Mahmud Dongoran - Mahmud Dongoran (Institut agama islam negeri Padangsidimpuan, 2015)
Maqasid syari’ah concept is the main discussion within Islamic law philosophy study. It says that public’s benefit and welfare are applied through Islamic law. There were Islamic clergies like Imam al-Haramain al-Juwaini (Usul al-fiqh expert), al-Gazali, and Muhammad Sa'id Ramadan al-Buti agreed about it. Moreover, there was then Islamic principle like where there is a benefit and welfare there is Allah’s law. In conclusion, the concept mainly proposes public’s goodness and against badness, public’s benefit and welfare, and against disadvantages. All of them are cores of Islamic law.